Identification of contaminating fungal DNA sequences in zymolyase - Rimek, Dagmar; Garg, Amar P.; Haas, Walter; Kappe, Reinhard (Journal of clinical microbiology, 1999)
When different preparations of Zymolyase were included in the pretreatment protocol of a panfungal PCR assay using a primer system for the 18S rRNA gene, an amplification product occurred in negative controls. The amplified fragment showed 100.0% sequence identity to the Saccharomyces sensu stricto complex andKluyveromyces lodderae. Lyticase, lysing enzymes, and proteinase K appeared to be free from fungal DNA.
Gesehen am 16.12.2020